2020
DOI: 10.1007/s11159-020-09820-7
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable learning and education: A curriculum for the future

Abstract: This article introduces sustainable learning and education (SLE), an emerging philosophy of learning and teaching founded on principles of sustainability. SLE is not necessarily education for sustainability, but rather sustainable learning, a new and different idea. The intention behind SLE is to create and proliferate sustainable curricula and methods of learning and teaching. These are designed to instil in people the skills and dispositions to thrive in complicated, challenging and ever-changing circumstanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 75 publications
2
46
0
4
Order By: Relevance
“…This study review also found that the above approaches agree with the principles of the Sustainable Learning and Education (SLE) philosophy (Hays & Reinders, 2020) that suggests integrating a 'sustainable environment, sustainable society, and sustainable economy' through the use of technology-mediated learning environment. The prerequisite for the SLE is a high degree of the individuals' computer literacy.…”
Section: Literature Reviewsupporting
confidence: 64%
“…This study review also found that the above approaches agree with the principles of the Sustainable Learning and Education (SLE) philosophy (Hays & Reinders, 2020) that suggests integrating a 'sustainable environment, sustainable society, and sustainable economy' through the use of technology-mediated learning environment. The prerequisite for the SLE is a high degree of the individuals' computer literacy.…”
Section: Literature Reviewsupporting
confidence: 64%
“…Studying parents' views is important, because it will help schools support collaboration with families in the future in similar circumstances and promote the support of sustainable education for children. Keeping this in mind, we discuss sustainability as a framework for sustainable learning and education that connects individual and organizational capacity for intentional, proactive, and collaborative learning [63].…”
Section: The Context Of the Researchmentioning
confidence: 99%
“…Sustainability in learning has also been defined in previous studies in terms of the transferability and usability of learning and knowledge (see Hays & Reinders, 2020;Tractenberg et al, 2016). In these studies, sustainable learning is learning that continues beyond the end of formal instruction (Tractenberg et al, 2016); it can be described as continuous learning situations and generating new understanding and means for learning (Kearney & Zuber-Skerritt, 2012; see also Prugsamatz, 2010).…”
Section: Widespread Use Of Previous Knowledgementioning
confidence: 99%
“…The most typical starting point is to see learning as a tool for environmentally or socially sustainable solutions (see, e.g., Albinsson & Arnesson, 2012;Kearney & Zuber-Skerritt, 2012;Scully-Russ, 2012), but there is a call for research on the sustainability of workplace learning situations themselves from a people perspective (Kira et al, 2010; see also Pfeffer, 2010;Gallagher et al, 2017). Therefore, in the current study, we approach the sustainability of the learning situation by paying attention to the perspectives of individual wellbeing (Di Fabio, 2016;Gallagher et al, 2017;Pfeffer, 2010), the wider use and recycling of existing knowledge (see Di Fabio, 2016, 2017Hays & Reinders, 2020;Tractenberg et al, 2016), as well as the rapid application of new knowledge (Brandi & Christensen, 2018).…”
Section: Introductionmentioning
confidence: 99%